(S)-Pramipexole and Its Enantiomer, Dexpramipexole : a New Chemoenzymatic Synthesis and Crystallographic Investigation of Key Enantiomeric Intermediates - Samuele Ciceri; Patrizia Ferraboschi; Paride Grisenti; Shahrzad Reza Elahi; Carlo Castellano; Matteo Mori; Fiorella Meneghetti (Catalysts, 2020)
A new chemoenzymatic method has been developed for the synthesis of (S)- and (R)-N-(6-hydroxy-4,5,6,7-tetrahydrobenzo[d]thiazol-2-yl) acetamide, two key synthons for the preparation of (S)-pramipexole, an anti-Parkinson drug, and its enantiomer dexpramipexole, which is currently under investigation for the treatment of eosinophil-associated disorders. These two building blocks have been obtained in good yields and high enantiomeric excess (30% and >98% ee for the R-enantiomer, and 31% and >99% ee for the S- one) through a careful optimization of the reaction conditions, starting from the corresponding racemic mixture and using two consecutive irreversible transesterifications, catalyzed by Candida antarctica lipase type A. Single crystal X-ray analysis has been carried out to unambiguously define the stereochemistry of the two enantiomers, and to explore in depth their three-dimensional features.